Analyzing The Effect Of BRICS On The Economic Growth Of Its Member - Shannen Surya Wibisono; Gabriella Grace Tanubrata; Ferry Vincenttius Ferdinand (Prodi Manajemen Universitas Pamulang, 2023)
This study aims to analyze the effect of BRICS membership on the economic growth of its countries, specifically its impact on GDP growth rate and international trade. This study uses data on the GDP growth rate, exports, and imports from 1997 to 2021 for BRIC countries and from 2001 to 2021 for South Africa. In addition, this study also used descriptive statistical analysis methods and Wilcoxon signed rank statistical test to see the significance of differences before and after member countries joined the BRICS. However, the analysis shows that not all BRICS member countries have significant differences in terms of GDP growth rate, exports, and imports. This divergence is due to several influencing factors, such as economic crises, wars, or conflicts. Thus, this research will provide a better understanding regarding the influence and effectiveness of the BRICS economic cooperation.